(untitled) (Research, Society and Development, 2022)
The study aims to demonstrate the care provided to pediatric patients in palliative care. It is an integrative literature review carried out through the databases Scientific Electronic Library Online (SciELO), Latin American and Caribbean Literature in Health Sciences (LILACS ) and Medical Literature Analysis and Retrieval System Online (MEDLINE), using the following Health Sciences Descriptors (DeCS): "palliative care" and "pediatric patient". Combined with each other by the Boolean operator AND. As inclusion criteria: articles available in full, in Portuguese, Spanish and English, that addressed the theme, in the last five years (2017-2022). As exclusion criteria: articles that did not contemplate the theme and repeated studies in the databases. 6206 articles were found, after the combined search of Boolean descriptors and operators, 9 articles were selected to compose the final sample. Palliative care is no longer at the opposite pole of healing therapy. The integration of the two models can grant higher life fines to families and to children with ongoing life-threatening illnesses. Recognizing and efficiently dealing with the most common signs and symptoms of patients, participating in a multidisciplinary team, developing a good relationship between the team, the family and the patients, and discussing problems associated with the abandonment of lifestyles are some of the fundamental foundations of palliative care.